2019
DOI: 10.1515/jpem-2018-0288
|View full text |Cite
|
Sign up to set email alerts
|

No clinical utility of common polymorphisms in IGF1, IRS1, GCKR, PPARG, GCK1 and KCTD1 genes previously associated with insulin resistance in overweight children from Romania and Moldova

Abstract: Background Previous genome-wide association studies (GWAS) identified IGF1, IRS1, GCKR, PPARG, GCK1 and KCTD1 as candidate genes for insulin resistance and type 2 diabetes (T2D). We investigated the associations of these previously reported common variants in these genes with insulin resistance in overweight children from Romania and Moldova. Methods Six single nucleotide polymorphisms (SNPs), IGF1 (rs35767), IRS1 (rs2943634), GCKR (rs780094), PPARG (rs1801282), GCK1 (rs1799884) and KCTD15 (rs29941), were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Our previous work [ 28 ] has already shown that a part of these risk factors are linked to increased carotid intima-media thickness (CIMT) and our goal is to provide more data on the links between these factors and vascular health. More studies are needed in order to determine the genetic profile of at-risk patients [ 29 ]. It is our aim to provide additional scientific data with regard to childhood obesity and other risk factors’ effects on arterial stiffness progression and ultimately, provide grounds for more efficient preventive measures and for an earlier intervention [ 30 ] in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work [ 28 ] has already shown that a part of these risk factors are linked to increased carotid intima-media thickness (CIMT) and our goal is to provide more data on the links between these factors and vascular health. More studies are needed in order to determine the genetic profile of at-risk patients [ 29 ]. It is our aim to provide additional scientific data with regard to childhood obesity and other risk factors’ effects on arterial stiffness progression and ultimately, provide grounds for more efficient preventive measures and for an earlier intervention [ 30 ] in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status across Europe is miscellaneous, but a high prevalence of childhood obesity has been reported throughout the entire continent, especially in Southern Europe ( 2 , 3 ). Overweight and obesity prevalence numbers in children from Romania are comparable to other European countries, with one recent study showing that every 1 in 4 individuals aged 6–19 years are overweight or obese ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 84%
“…Some studies in adults have reported an association between the Ala12 variant of PPARγ2 gene and a minor risk of diabetes and insulin resistance ( Ek et al, 2001 ; González Sánchez et al, 2002 ), although some others failed to find any association ( Mancini et al, 1999 ). Also studies in children have found an association between the polymorphism and insulin sensitivity ( Buzzetti et al, 2005 ; Scaglioni et al, 2006 ; Dedoussis et al, 2009 ; Jermendy et al, 2011 ), although others failed to find this association ( Johansson et al, 2009 ; De Kort and Hokken-Koelega, 2010 ; Csernus et al, 2015 ; Stryjecki et al, 2016 ; Chirita-Emandi et al, 2019 ). However, most of the studies analyzed data in a dominant model ( Stumvoll et al, 2001 ) and reported significant associations in subjects with obesity ( Hara et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%